2018
DOI: 10.1016/j.colsurfb.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring weight ratio of PCL/PLA in electrospun three-dimensional nanofibrous scaffolds and the effect on osteogenic differentiation of stem cells

Abstract: Three-dimensional (3D) scaffolds as artificial ECMs have been extensively studied to mimic the critical features of natural ECMs. To develop more clinically relevant 3D scaffolds, electrospun nanofibrous scaffolds with different weight ratios of PCL/PLA (i.e., 100/0, 60/40, and 20/80) were fabricated via the thermally induced (nanofiber) self-agglomeration (TISA) method. The hypothesis was that, with the weight ratio increase of stiffer and more bioactive PLA in the 3D PCL/PLA blend scaffolds, the osteogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 50 publications
(46 reference statements)
0
56
0
Order By: Relevance
“…They have found that a core-shell electrospinning to fabricate a PCL/PLLA scaffold with hydroxyapatite particles allowed an osteoconductive environment and also induced differentiation of human mesenchymal stem cells (hMSCs). A similar study by Xu and co-workers [154] used a PCL/PLA electrospun composite, but they specifically saw that an increase in the PLA content induced a higher alkaline phosphatase and calcium deposition due to the higher stiffness of the scaffold. The same group also saw a higher osteogenic differentiation of hMSCs in vitro and more functional cranial bone formation in vivo due to this PCL/PLA blend [155].…”
Section: Bioscaffolds For Cell Cultivation In Vitromentioning
confidence: 96%
“…They have found that a core-shell electrospinning to fabricate a PCL/PLLA scaffold with hydroxyapatite particles allowed an osteoconductive environment and also induced differentiation of human mesenchymal stem cells (hMSCs). A similar study by Xu and co-workers [154] used a PCL/PLA electrospun composite, but they specifically saw that an increase in the PLA content induced a higher alkaline phosphatase and calcium deposition due to the higher stiffness of the scaffold. The same group also saw a higher osteogenic differentiation of hMSCs in vitro and more functional cranial bone formation in vivo due to this PCL/PLA blend [155].…”
Section: Bioscaffolds For Cell Cultivation In Vitromentioning
confidence: 96%
“…Studies have been conducted for culturing BMSCs onto scaffolds in order for cells to differentiate into osteoblast progenitors and promote bone formation. Liu et al [67] reported on a chitosan/HA composite, and Xu et al [101] reported on a PCL/PLLA composite. Both studies described the use of scaffolds combined with BMSC for bone regeneration.…”
Section: Biodegradable Scaffolds As Drug Delivery Systemsmentioning
confidence: 99%
“…Research has been conducted to cultivate BMSC on scaffolds to differentiate into osteoblast progenitor cells and promote bone formation. Liu et al reported on a chitosan/HA composite [66], while Xu et al reported on a PCL/PLLA composite [81] that combines nanofibers and BMSC for bone regeneration.…”
Section: Cells For Bone Regeneration and Signaling Moleculesmentioning
confidence: 99%